2015
DOI: 10.1063/1.4938028
|View full text |Cite
|
Sign up to set email alerts
|

Realistic vs sudden turn-on of natural incoherent light: Coherences and dynamics in molecular excitation and internal conversion

Abstract: Molecular excitation with incoherent light is examined using realistic turn-on time scales, and results are compared to those obtained via commonly used sudden turn-on, or pulses. Two significant results are obtained. First, in contrast to prior studies involving sudden turn-on, realistic turn-on is shown to lead to stationary coherences for natural turn-on time scales. Second, the time to reach the final stationary mixed state, known to result from incoherent excitation, is shown to depend directly on the inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…(4) that depends on the field properties is the total occupation number operator. Therefore, to obtain a time-dependent intensity expectation value, the radiation field density matrix must change over time such that n kλ (t) = n kλ (t) = Tr R {n kλρR (t)} = n kλ f (t) (5) where Tr R is the trace over the radiation field. The turn on function must be identical for all modes due to the restrictions from Eqs.…”
Section: A Properties Of Field Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…(4) that depends on the field properties is the total occupation number operator. Therefore, to obtain a time-dependent intensity expectation value, the radiation field density matrix must change over time such that n kλ (t) = n kλ (t) = Tr R {n kλρR (t)} = n kλ f (t) (5) where Tr R is the trace over the radiation field. The turn on function must be identical for all modes due to the restrictions from Eqs.…”
Section: A Properties Of Field Dynamicsmentioning
confidence: 99%
“…Those associated with, for example, donor excitation in a donor-acceptor system, briefly discussed in [5], will be discussed in detail elsewhere [27,28]. Further, these studies do not include, but do motivate including, a second bath that would model, e.g., a bosonic environment.…”
Section: Introductionmentioning
confidence: 99%
“…This non-secular regime commonly appears in many atomic and molecular systems. For example, large molecules with 10's of atoms typically have dense manifolds of closely spaced excited vibronic states that fall within the non-secular regime [8,10,11,18,23,27]. Similarly, the angular momentum p states of atomic systems in weak magnetic fields, discussed below, are typically nearly degenerate and also fall within this regime [9,19].…”
Section: Noise-induced Coherences a Simultaneous Excitation And Non-s...mentioning
confidence: 99%
“…By contrast, incoherent light excites a statistical mixture of eigenstates [15][16][17]. Because incoherent light is stationary, it, strictly speaking, exists only as a continuous-wave process (various artefacts are present if incoherent light is suddenly switched on [35][36][37][38][39][40]). However, Jesenko and Žnidarič have shown that the efficiency of light harvesting in continuous-wave incoherent light is equal to the efficiency given a particular transient initial state [41].…”
mentioning
confidence: 99%